1988
DOI: 10.1159/000125023
|View full text |Cite
|
Sign up to set email alerts
|

Daily Melatonin Injections Affect the Expression of Circadian Rhythmicity in Djungarian Hamsters Kept under a Long-Day Photoperiod

Abstract: Djungarian hamsters (Phodopus sungorus) kept under a long-day photoperiod (16 h light :8 h dark) were injected with melatonin each day. Hamsters which responded physiologically to this treatment (gonadal regression, molt, body weight loss) phase-advanced onset and extended duration of activity. Hamsters which were physiologically insensitive to melatonin injections did not exhibit such changes in activity pattern and often failed to entrain to the light :dark cycle. Hamsters given saline injections did not alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…In a related study, however, Puchalski and Lynch (1988b) found that refractoriness to daily melatonin injections (as determined by molt from a white to a greybrown pelt, body weight gain, and gonadal recrudescence) occurred at about weeks 26-32 of hormone treatment. Furthermore, they found that shifts in phase angle and a occurred simultaneously with changes in body weight, molt, and gonadal state.…”
Section: Discussionmentioning
confidence: 92%
“…In a related study, however, Puchalski and Lynch (1988b) found that refractoriness to daily melatonin injections (as determined by molt from a white to a greybrown pelt, body weight gain, and gonadal recrudescence) occurred at about weeks 26-32 of hormone treatment. Furthermore, they found that shifts in phase angle and a occurred simultaneously with changes in body weight, molt, and gonadal state.…”
Section: Discussionmentioning
confidence: 92%
“…Pineal dependence of innate immunity has been inferred from a study which maintained hamsters in constant light, suppressing endogenous melatonin secretion (Yellon et al, 2005); pineal dependence of adaptive immunity has been inferred from an experiment which exposed pinealectomized hamsters to short days for 1 week prior to antigenic challenge (Yellon et al, 1999b). The interpretation of these studies is not straightforward, given that: (1) daily melatonin injections also render the circadian system in a SD-typical state (Puchalski and Lynch, 1988;Margraf and Lynch, 1993), (2) little is known regarding the significance of the amplitude of melatonin signals on immune function, and (3) constant light renders circadian rhythms in a free-running state, functions as a stressor, and can be immunosuppressive (Morimoto et al, 1975;Ramaley, 1977;Larsen et al, 1994;Liebmann et al, 1996). An alternative, and definitive, approach is to determine whether photoperiodic responses in the immune system endure following removal of the endogenous pineal melatonin signal (via surgical pinealectomy) and exposure to longer seasonal intervals of short days (>6 weeks).…”
Section: Introductionmentioning
confidence: 99%
“…In the Djungarian hamster, gonadal regression or lengthening the duration of nocturnal locomotor activity requires repeated administration of melatonin for several weeks (Puchalski and Lynch, 1988). In the rat, more than a week of daily melatonin injections are needed to entrain or reinstate circadian locomotor activity under constant photoperiodic conditions .…”
Section: Introductionmentioning
confidence: 99%